Síntese e avaliação biológica de novos derivados anti-inflamatórios esteroides - Machado, Marcella Gabrielle Mendes [UNESP] (2013)
Inflammation is characterized as a organism response against an aggression, which can result in pain, edema and in some cases lead to organ or tissue dysfunction. During the inflammatory process are released of cytokines, small proteins transcribed and translated by intrinsic cellular metabolism, performing a variety of communication intra and intercellular. An important cytokine is tumor necrosis factor alpha (TNF-α), which acts in maintaining the inflammatory in situations of chronic inflammation, being over expressed in many inflammatory diseases. Therapy anti-tumor necrosis factor α (anti-TNF-α) has become an interesting approach in the treatment of chronic inflammatory diseases, especially those patients who do not respond to conventional treatment. Among the drugs used in the treatment of chronic inflammatory diseases are glucocorticoids (GCs), anti-inflammatory steroids. These act in the reactive process of organism defense minimizing the damage caused by the infectious agent. However, prolonged use of GCs is associated with various side effects such as osteoporosis, metabolic syndrome, cardiovascular disease, cataracts, among others, limiting the use of these drugs in prolonged therapies. Thus, in this work, we realized the viability of design and synthesis by molecular hybridization strategy of novel anti-inflammatory steroids with modulating properties of cytokine TNF-α in order to achieve a synergism of action useful in the treatment of diseases chronic inflammatory diseases. In this context, were synthesized and characterized six compounds Lapdesf series GL-FT derived from glucocorticoids prednisolone (compounds I-III) and budesonide (compounds IV-VI), connected to the phthalimide group responsible for inhibition of TNF-α. The obtained compounds were evaluated for anti-inflammatory activity in a model of paw edema and distal ulcerative colitis. Derivatives I and IV showed higher ...